An efficient CSMA/CA protocol for IEEE 802.11 - Hussein Abbas, Ali Muhammad (2018)
Since their emergence within the past decade, wireless networks have been adapted to enable mobility, and become increasingly popular in the world. Then, WLANs were introduced and mainly used to enhance mobility. Undoubtedly, its popularity has been increasing worldwide. The most important standard in WLANs is IEEE 802.11. This standard involves the concurrent use of equipment, thus permitting higher frequency range. Its coding technique is efficient, and its implementation cost is relatively low. As a result, most of the research works related to the enhancement of WLANs are designed based on the IEEE 802.11 standard. However, there are unresolved issues related to the performance metrics such as collision rate and throughput. IEEE 802.11 standard is a set of MAC protocols and physical layer specifications for implementing WLAN computer communication. MAC protocol plays an important role in accessing the transmission medium and the data transmission of wireless stations. Thus, the MAC protocol should be enhanced in order to increase the IEEE 802.11 network performance when the number of users increases. In the current work, the main aim was to enhance the performance of the 802.11 standard using an efficient CSMA/CA MAC protocol. The transmission mechanism of CSMA/CA protocol is based on the contention window (backoff range). According to the literature, the current CSMA/CA protocols do not consider the accuracy of contention window by researchers so far. In other words, the practical network operation has not been taken into account. The possibility of contention window change rate becoming larger/smaller than that required has been neglected. In either case, the channel is not efficiently used, thus degrading the system performance. In this study, both the accuracy of the contention window and the network condition were taken into account. In order to consider the accuracy of the contention window, a proposed protocol was introduced using three control parameters in order to determine the required change rate of the contention window. In addition, the proposed protocol employs a reference point for the collision rate in order to determine the network contention level. Thus, the contention window was adjusted based on the required change rate in order to reflect the number of active stations in the network. The proposed protocol and the assumed scenarios were implemented in the OPNET simulator by using the advanced wireless library (WLAN module). The simulator was used to evaluate the performance metrics of the proposed protocol, i.e. collision rate, throughput, and data drop. The performance results have highlighted the importance of taking into account the accuracy of the contention window. In fact, the performance of the proposed protocol was better than other protocols. The collision rate decreased by 6% and throughput underwent 4% increment upon using the proposed protocol.